Roburic Acid Targets TNF to Inhibit the NF-κB Signaling Pathway and Suppress Human Colorectal Cancer Cell Growth - Xu, Huanhuan; Liu, Titi; Li, Jin; Chen, Fei; Xu, Jing; Hu, Lihong; Jiang, Li; Xiang, Zemin; Wang, Xuanjun; Sheng, Jun (Frontiers in Immunology, 2022)
Tumor necrosis factor (TNF)-stimulated nuclear factor-kappa B (NF-κB) signaling plays very crucial roles in cancer development and progression, and represents a potential target for drug discovery. Roburic acid is a newly discovered tetracyclic triterpene acid isolated from oak galls and exhibits anti-inflammatory activity. However, whether roburic acid exerts antitumor effects through inhibition of TNF-induced NF-κB signaling remains unknown. Here, we demonstrated that roburic acid bound directly to TNF with high affinity (KD = 7.066 μM), blocked the interaction between TNF and its receptor (TNF-R1), and significantly inhibited TNF-induced NF-κB activation. Roburic acid exhibited antitumor activity in numerous cancer cells and could effectively induce G0/G1 cell cycle arrest and apoptosis in colorectal cancer cells. Importantly, roburic acid inhibited the TNF-induced phosphorylation of IKKα/β, IκBα, and p65, degradation of IκBα, nuclear translocation of p65, and NF-κB-target gene expression, including that of XIAP, Mcl-1, and Survivin, in colorectal cancer cells. Moreover, roburic acid suppressed tumor growth by blocking NF-κB signaling in a xenograft nude mouse model of colorectal cancer. Taken together, our findings showed that roburic acid directly binds to TNF with high affinity, thereby disrupting its interaction with TNF-R1 and leading to the inhibition of the NF-κB signaling pathway, both in vitro and in vivo. The results indicated that roburic acid is a novel TNF-targeting therapeutics agent in colorectal cancer as well as other cancer types.